Stok Karbon pada Berbagai Umur Kelapa Sawit Perkebunan Kelapa Sawit - Yuniasih, Betti; Syaputra, Fitra Nuryandri; Hartati, Retni Mardu (Program Studi Agroteknologi INSTIPER, 2025)
Oil palm plantations are one of the important carbon stocks for climate change mitigation because of their ability to store carbon and absorb free carbon from the air. This study aims to calculate carbon stocks at various stages of oil palm growth. The samples in this study were oil palm producing plants with various age classes; young plants (3-8 years), juvenile plants (9-14 years), and old plants (> 21 years) taken with a sample of 3 plots with 1 plot of 10 trees each in each age class variation using a quadrant (sample plot) plot size of 20 x 60 m with 3 replications. The sampling of understory vegetation was carried out in a measurement plot with a size of 1 m x 1 m as much as 1 sample placed in each plot of oil palm stand biomass measurement. The study was conducted using a carbon stock measurement method with a non-destructive approach using an allometric equation. In young, juvenile, and old oil palm plants. on sample plots according to the predetermined age groups. The research samples were selected by purposive sampling. In each sample, carbon stocks were measured in the oil palm plants and floor vegetation carbon stocks. The results of the study showed that carbon stock analysis showed a close relationship with plant age. Oil palm plant carbon stocks continued to increase with increasing plant age. Therefore, it can be concluded that oil palm biomass increases with increasing age in young plants (3.77 tons/ha), adolescents (12.61tons/ha), and old (>21 years, 167.82 tons/ha).